Salacca zalacca: a short review of the palm botany, pharmacological uses and phytochemistry - Saleh, Mohammed S M; Siddiqui, Mohammad Jamshed Ahmad; Mediani, Ahmed; Ismail, Nor Hadiani; Ahmed, Qamar Uddin; Mat So'ad, Siti Zaiton; Saidi-Besbes, Salima (Wolters Kluwer ‐ Medknow, 2018)
Salacca zalacca (Gaertn.) Voss (family Arecaceae) is the snake fruit commonly known in Malay language as salak in Malaysia. This exotic fruit has diverse and potential pharmacological properties due to its high antioxidant content. It is often consumed due to its sweet taste. The abundant natural sugar and fibre along with minerals and vitamin makes it a nutritious fruit. Phytochemical investigation on this fruit has revealed the presence of flavonoids, phenolics, glycosides as well as some volatile and aromatic compounds, including gallic acid, quercetin, chlorogenic acid, epicatechin, proanthocyanidins, lycopene and β-carotene. Pharmacological studies on the fruit flesh and peel have shown some tremendous antioxidant, anti-inflammatory, anticancer and antidiabetic potential. This review provides the botanical information of Salacca zalacca as well as its scientific investigations involving the distinct pharmacological and phytochemical benefits. This could help in highlighting the lacking data and research gaps on this plant